Actual Problems of Kartvelology and Objectives of the Kartvelological Centre of Saint Andrew the First-Called Georgian University of the Patriarchate of Georgia - Putkaradze, Tariel (Actual Problems of Kartvelology, 2025)
A great empire has a lot of impressive resources for planning and managing according to its own interests science on the conquered small nations as well. Unfortunately, Kartvelology could not have escaped such impacts either. Like other disciplines, Kartvelology has developed intensively during the last two centuries. Over that period Georgia was mostly annexed by the Russian Empire, respectively, over the last 150 years two radically different approaches towards planning and development of Kartvelology have clearly taken shape: 1. Quasi-Kartvelology oriented on the geopolitical interests of the empire;1 2. Scholarly Kartvelology oriented on the vital interests of the Georgian nation